Colorectal cancer development and advances in screening - Balchen, Vanessa; Simon, Karen (Clinical interventions in aging, 2016)
Most colon tumors develop via a multistep process involving a series of histological, morphological, and genetic changes that accumulate over time. This has allowed for screening and detection of early-stage precancerous polyps before they become cancerous in individuals at average risk for colorectal cancer (CRC), which may lead to substantial decreases in the incidence of CRC. Despite the known benefits of early screening, CRC remains the second leading cause of cancer-related deaths in the United States. Hence, it is important for health care providers to have an understanding of the risk factors for CRC and various stages of disease development in order to recommend appropriate screening strategies. This article provides an overview of the histological/molecular changes that characterize the development of CRC. It describes the available CRC screening methods and their advantages and limitations and highlights the stages of CRC development in which each screening method is most effective.